Notes on Early Land Plants Today. 11. Microlejeunea bischlerae (B.M.Thiers) comb. nov. - Thiers, Barbara M.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
In the past the genus Microlejeunea Stephani (1888) has often been regarded as a subgenus of Lejeunea Libert (1820). Lejeunea bischlerae Thiers (1997) was described using this concept. However, recent molecular studies (e.g. Wilson et al. 2004) resolve Microlejeunea as a sister of Lejeunea. If this concept is followed, a new combination is needed.